Economic Efficiency of Means for Mechanization in Agricultural Complex - BATYROVA, Nazygul; FATIH, Turkmen; YERMANKULOVA, Rima (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
Mechanization of production is associated with the use of technological advances and scientific discoveries based on the development of the natural sciences. The most important areas of scientific and technological progress and the creation of new means of labor are: the further development of synthesis, direct energy conversion, the depth of processing of raw materials and the protection of the environment. Therefore, the main objective of the work is to analyze the problems and the main advantages in the use of mechanization tools in agriculture. The authors found that agriculture plays a significant role in the country's economy and directly affects its structure and level of development. It has been determined that the adaptation of modern technologies and means of mechanization should be carried out systematically on the basis of the formation of information data sets on basic technologies, varieties, soils, and technology.